Plasma exchange effectively removes 52‐ and 60‐kDa anti‐Ro/SSA and anti‐La/SSB antibodies in pregnant women with congenital heart block. Issue 7 (30th March 2015) - Tonello, Marta; Ruffatti, Amelia; Marson, Piero; Tison, Tiziana; Marozio, Luca; Hoxha, Ariela; De Silvestro, Giustina; Punzi, Leonardo
<x xml:space="preserve">Abstract</x> BACKGROUND Pregnant women positive for 52‐ and 60‐kDa anti‐Ro/SSA and anti‐La/SSB antibodies can suffer from congenital heart block (CHB), a passively acquired autoimmune disease. STUDY DESIGN AND METHODS We evaluated the efficacy of plasma exchange (PE) in removing 52‐ and 60‐kDa anti‐Ro/SSA and anti‐La/SSB antibodies in pregnant women with CHB treated with a combined therapy including PE, intravenous immunoglobulins, and steroids. Antibody levels were monitored in 10 consecutive pregnant women diagnosed with CHB and prospectively followed between 2009 and 2013. Assaying was performed using a homemade enzyme‐linked immunosorbent assay test on blood samples collected immediately before and after PE sessions. RESULTS A significant decrease in mean post‐PE antibody levels was noted in all the cases examined. An analysis of antibody level trends in the samples collected before PE sessions showed that there was a steady, significant decrease in 90% of the patients with 52‐kDa anti‐Ro/SSA, in 80% of those with 60‐kDa anti‐Ro/SSA antibodies, and in 100% of those with anti‐La/SSB antibodies. CONCLUSION This study demonstrates that PE is effective in removing antibodies linked to the pathogenesis of CHB. PE treatment was found to have a long‐term efficacy in all the women positive for anti‐La/SSB antibodies and in most of the women positive for 52‐ and 60‐kDa anti‐Ro/SSA antibodies. It is interesting that the significant, immediate, and long‐term fall in antibody levels that was observed in these patients took place in all the women whose CHB was reversed. This finding could give PE an important role in the treatment of CHB.